Application of Ribosomal RNA Gene Restriction Patterns Analysis and Pulsed-Field Gel Electrophoresis in Distinguishing Salmonella Weltevreden Isolates in Malaysia - Goh, Yee Ling; Puthucheary, Savithri Devi; Thong, Kwai Lin (SEAMEO Regional Tropical Medicine and Public Health Network, 2000)
A representative sample of 20 isolates of Salmonella weltevreden strains from stool cultures of patients admitted at the University Hospital, Kuala Lumpur, Malaysia were analyzed. All the strains were susceptible to ampicillin, ceftriaxone, ciprofloxacin, chloramphenicol, tetracycline, trimethoprim, gentamicin and co-trimoxazole. Ribosomal RNA gene restriction pattern analysis of PstI-digested DNA gave three ribotypes while pulsed-field gel electrophoresis (PFGE) analysis of XbaI-digested DNA gave ten distinct profiles. PFGE was more discriminative than ribotyping in distinguishing the strains. The majority of the strains analyzed were very closely related with similarity coefficient values ranging from 0.8 to 1.0. Both PFGE and ribotyping could distinguish one of the strains which was obtained from a patient following a bone marrow transplant for Î²-thalassemia major, indicating that this particular strain was unrelated to the rest of the strains from patients with acute gastroenteritis.